WEB APPLICATION DEVELOPMENT USING THE PEAR LIBRARY - Pańczyk, Beata; Duszyk, Michał (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
The paper presents the possibility of the PEAR library in the rapid production of the PHP applications. The advantages and benefits of the use of the PEAR are going to be presented. Use of this repository class library can significantly simplify and optimize the PHP code and accelerate the process of the web application programming.